Efficient and Color Stable White Quantum‐Dot Light‐Emitting Diodes with External Quantum Efficiency Over 23%. Issue 16 (25th June 2018) - Zhang, Heng; Su, Qiang; Sun, Yizhe; Chen, Shuming
Abstract: White quantum dot light‐emitting diodes (WQLEDs) with different structures are developed. By mixing red (R), blue (B) and green (G) quantum dots (QDs) together, the optimal WQLEDs exhibit a peak current efficiency (CE) of 22.54 cd/A and an external quantum efficiency (EQE) of 7.07%. The relatively poor performance is due to the efficient nonradiative Förster resonant energy transfer (FRET) among B‐, G‐ and R‐QDs. To address this issue, tandem WQLEDs are developed. By stacking the blue and the yellow QLEDs, the two‐unit tandem WQLEDs exhibit a peak CE of 30.3 cd/A and a maximum EQE of 15.2%. To further improve the color stability and the efficiency, the R/G/B three‐unit tandem WQLEDs are developed, which exhibit an impressive CE of 55.06 cd/A, a high EQE of 23.88% and a high luminance of 65690 cd/m 2, which are the highest values ever reported. Moreover, the optimal tandem WQLED exhibits a high color stability, a pure white color with a 1931 Commission International de I'Eclairage (CIE) coordinate of (0.33, 0.34) and a color rendering index of 80. The demonstrated tandem WQLEDs, with high efficiency, pure white color, high color stability and high color‐rendering, would be promising candidates for next generation solid‐state lighting and full‐color display. Abstract : Highly efficient and color stable white quantum‐dot light‐emitting diodes are demonstrated by using a three‐unit tandem structure, which exhibit a pure white emission and an impressively high external quantum efficiency of 23%.